Like family : narratives of fictive kinship - Nelson, Margaret K., 1944- (Families in focus., 2020)
"For decades, social scientists have assumed that "fictive kinship" is a phenomenon associated only with marginal peoples and people of color in the United States. In this innovative book, Nelson reveals the frequency, texture and dynamics of relationships which are felt to be "like family" among the White, middle-class"--